Association between vitamins and risk of brain tumors: A systematic review and dose-response meta-analysis of observational studies - Zhang, Weichunbai; Jiang, Jing; He, Yongqi; Li, Xinyi; Yin, Shuo; Chen, Feng; Li, Wenbin (Frontiers in Nutrition, 2022)
Background: Brain tumor is one of the important causes of cancer mortality, and the prognosis is poor. Therefore, early prevention of brain tumors is the key to reducing the mortality of brain tumors. Objective: This review aims to quantitatively evaluate the association between vitamins and brain tumors by meta-analysis. Methods: We searched articles on PubMed, Cochrane Library, Web of Science, and EMBASE from inception to 19 December 2021. According to heterogeneity, the fixed-effects model or random-effects model was selected to obtain the relative risk of the merger. Based on the methods described by Greenland and Longnecker, we explored the dose-response relationship between vitamins and the risk of brain tumors. Subgroup analysis, sensitivity analysis, and publication bias were also used for analysis. Results: The study reviewed 23 articles, including 1347426 controls and 6449 brain tumor patients. This study included vitamin intake and circulating concentration. For intake, it mainly included vitamin A, vitamin B, vitamin C, vitamin E, β-carotene, and folate. For circulating concentrations, it mainly included vitamin E and vitamin D in serum (25-hydroxyvitamin D and α-tocopherol). For vitamin intake, compared with the lowest intakes, the highest intakes of vitamin C (RR=0.81, 95%CI:0.66-0.99, I2=54.7%, P for heterogeneity=0.007), β-carotene (RR=0.78, 95%CI:0.66-0.93, I2=0, P for heterogeneity=0.460), and folate (RR=0.66, 95%CI:0.55-0.80, I2=0, P for heterogeneity=0.661) significantly reduced the risk of brain tumors. For serum vitamins, compared with the lowest concentrations, the highest concentrations of serum α-tocopherol (RR=0.61, 95%CI:0.44-0.86, I2=0, P for heterogeneity=0.656) significantly reduced the risk of brain tumors. The results of the dose-response relationship showed that increasing the intake of 100μg folate per day reduced the risk of brain tumors by 7% (P-nonlinearity=0.534, RR=0.93, 95%CI:0.90-0.96). Conclusions: Our analysis suggests that the intake of vitamin C, β-carotene, and folate can reduce the risk of brain tumors, while high serum α-tocopherol concentration also has a protective effect on brain tumors. Therefore, vitamins may provide new ideas for the prevention of brain tumors.